ICTs and the Internet as a Framework and Field in Ethnographic Research - Tummons, Jonathan (Acta Paedagogica Vilnensia, 2017)
In this article, I offer a reflexive account drawing on my role as co-investigator based on a three-year institutional ethnography: Medical Education in a Digital Age. Three problematic issues are discussed: first, the ways by which a reliance on digital technologies for communication between members of the research team impacted on the researchers’ discourse; second, the ways by which the multi-sidedness and distributed nature of the ethnography (in terms of field as well as research team) can be theorized; and third, the extent to which differing “traditions” of ethnographic methodology (such as “digital” ethnography and “virtual” ethnography) satisfactorily explicate the standpoint taken by the researchers as both individuals and as members of a research team.
Keywords: ethnography; methodology; reflexivity; technology